Evaluation of construction sustainability by multiple criteria methods - Šaparauskas, Jonas; Turskis, Zenonas (Technological and Economic Development of Economy, 2006)
Sustainable construction is a relevant subject in contemporary world because it is one of approaches achieving sustainability in all the spheres of society development. The authors reveal difficulties which emerge in creating the indicator system for sustainability evaluation, searching for information concerning indicators and in making mathematical calculations. After thorough analysis of research papers, specific databases and other information sources an algorithm for indicator system creation was suggested. The set of construction sustainability indicators for a particular country was built, the values of indicators were defined and then several decision‐making methods were applied. According to a general index of construction sustainability, a conclusion was drawn about construction state in the context of sustainable development.Statybos darnos vertinimas daugiakriteriniais metodaisSantrauka. Darnioji statyba – aktuali tema šiuolaikiniame pasaulyje, nes tai yra vienas būdų, siekiant darnaus vystymosi visose visuomenės raidos sferose. Autoriai atskleidžia sunkumus, kurie atsiranda, kuriant statybos darnos įvertinimo rodiklių sistemą, renkant informaciją apie rodiklius ir atliekant matematinius skaičiavimus. Atlikus išsamią mokslinių šaltinių analizę, pasiūlyta statybos darnos rodiklių sistemos sudarymo loginė schema. Sudaryta konkrečios šalies statybos darnos rodiklių sistema ir nustatytos rodiklių reikšmės, pritaikyti keli sprendimų priėmimo metodai. Pagal kelerių metų statybos darnos kompleksinio rodiklio reikšmes daroma išvada apie statybos būklę darnaus vystymosi kontekste.Reikšminiai žodžiai: darnioji statyba, darnus vystymasis, įvertinimas, rodiklių sistema, sprendimų priėmimo metodai.First Published Online: 21 Oct 2010